Aktualisasi Nilai-Nilai Pancasila dalam Anggaran Dasar/Anggaran Rumah Tangga Dharmawanita Persatuan Kecamatan Panggungrejo Kabupaten Blitar - Natalia Mega Dharma; M. Iqbal Baihaqi; Arik Cahyani (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2026)
This study aims to analyze the actualization of Pancasila values in the Articles of Association and Bylaws (AD/ART) of the Dharma Wanita Persatuan (DWP) in Panggungrejo District, Blitar Regency. The study used a qualitative approach with a phenomenological design to understand the experiences and views of informants regarding the application of Pancasila values in organizational practice. Data were collected through structured interviews, field observations, organizational documentation, and validated using triangulation of sources, techniques, and time. The results show that material values are reflected in operational discipline, mutual cooperation, and transparency in resource management; vital values are manifested through the AD/ART as guidelines for work and the implementation of educational, social, and empowerment programs; while moral values are evident through communication ethics, the practice of deliberation and consensus, and strengthening solidarity among members. These findings confirm that the AD/ART functions as a connecting instrument that integrates material, vital, and moral values, thereby creating an organizational structure that aligns with Pancasila. This study has important implications for strengthening the character and ethics of organizations based on national values at the local level.